Efektivitas Manga Doraemon sebagai Media Pembelajaran Terhadap Penguasaan Hiragana pada Siswa SMAN 4 Pekanbaru - Dheo Jaya Dipa; Merri Silvia Basri; Adisthi Martha Yohani (KIRYOKU, 2023)
This study aims to view the effectiveness of using Doraemon’s manga as a learning media on comprehend of hiragana in class XI of  sman 4 Pekanbaru. The population of this study were 72 students of class XI of  SMAN 4 Pekanbaru with samples taken of 36 students which were divided into 18 students for the experimental class and 18 students for the control class. The results obtained were based on the independent sample T-Test on the Post-Test results of the two classes, namely 0.016 and showed that Doraemon’s manga as a learning media was proven to be effective on comprehend hiragana of class XI of SMAN 4 Pekanbaru.